Silk fibroin promotes mineralization of gellan gum hydrogels - Kundu, Banani (2020)
Mineralization is a natural process leading to the formation of mineralized tissue such as bone. The chief mineral component of bone is hydroxyapatite (HAp), which is deposited using an organic template like fibrillar Collagen I under physiological condition. Fibrous silk fibroin is structurally homologous to collagen and acts as nucleation site for HAp mineralization when immersed in simulated body fluid (SBF) or fetal bovine serum (FBS), therefore, considered as popular bone regeneration biomaterial. Hence, the mineralization behavior of silk fibroin self-assembled gellan gum enriched 3D hydrogels is investigated under conditions closer to physiological ones using SBF as well as FBS, and also in presence of cells (e.g. human adipose tissue-derived stem cells, ASCs). Incorporation of silk fibroin induces the mineralization in acellular spongy-like hydrogels in composition dependent manner, confirmed by SEM-EDS analysis. In contrast, ASCs mediated mineralization is found in all hydrogel compositions of 3Â weeks post-culture under osteogenic conditions as demonstrated by gene expression profile and Alizarin Red S staining. This is perhaps due to the co-existence of fibroin and FBS together induce cell-mediated mineralization. The blending of fibroin offers cheap alternative strategy to improve or guide the repair of mineralized tissue using gellan gum-based biomaterials.